2010
DOI: 10.1002/smi.1309
|View full text |Cite
|
Sign up to set email alerts
|

Burnout as an important factor in the psychophysiological responses to a work day in Teachers

Abstract: Burnout syndrome is an important psychosocial risk in the job context, especially in professions with a strong social interaction, as in the case of teaching. This study analyses the role of burnout in the psychophysiological responses to a work day in teachers. High burnout was related to worse mood, and higher perceived stress throughout the work day. Moreover, burnout is positively related to systolic blood pressure and negatively related to salivary cortisol levels at the beginning of the work day. Higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
(46 reference statements)
1
19
0
Order By: Relevance
“…In fact, in WD2 C is less pronounced during the morning and the evening compared to WD1. In addition, reduction in diurnal C amplitude was seen in a large study of groups reporting increased levels of stress (Rosmond, Dallman, & Björntorp, 1998), in subjects with burnout (Pruessner, Hellhammer & Kirschbaum, 1999, Moya-Albiol et al 2010a) and in female teachers with allostatic load (Bellingrath, Weigl & Kudielka, 2009). Dahlgren et al (2006) concluded that fatigue and exhaustion may be related to individual differences in the C response to stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, in WD2 C is less pronounced during the morning and the evening compared to WD1. In addition, reduction in diurnal C amplitude was seen in a large study of groups reporting increased levels of stress (Rosmond, Dallman, & Björntorp, 1998), in subjects with burnout (Pruessner, Hellhammer & Kirschbaum, 1999, Moya-Albiol et al 2010a) and in female teachers with allostatic load (Bellingrath, Weigl & Kudielka, 2009). Dahlgren et al (2006) concluded that fatigue and exhaustion may be related to individual differences in the C response to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been observed that negative mood autorregulation has positive effects on the way of coping with stressful events in a working day (Mearns & Cain, 2003). In this sense, negative mood and PS has been positively related to burnout during a working day (Moya-Albiol, Serrano & Salvador, 2010a) and in stress situations (Flynn & James, 2009). Furthermore, positive affect is related to favorable profiles of functioning in several biological systems (Steptoe & Wardle, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…140,141,143 Two studies assessed perceived stress based on a single question 140,141 and 1 study developed more elaborate questionnaires. 143 All studies except 1 used a reliable method of blood pressure measurement.…”
Section: Non-validated Perceived Stress Measures: No Associationmentioning
confidence: 99%